Pharmacists' Perceptions on Safety Alerts of the Drug Utilization Review (DUR) in Electronic Health Records in a Tertiary Healthcare Hospital - Nouf Alshehri; Abdullah Alanazi (MDPI AG, 2023)
Electronic Drug Alarms and Drug Utilization Reviews (DURs) are crucial in improving patient safety by reducing the dispensing of contraindicated medications and minimizing adverse drug events. The DUR system often generates low-level alerts, making it challenging for pharmacists and doctors to discern more critical alerts. This can result in alert fatigue, causing burnout and jeopardizing patient safety. A cross-sectional study was conducted in a tertiary hospital to explore pharmacists' perspectives and experience with the DUR system. This study aimed to identify their responses to alerts indicating a need to change the original prescription and the difficulties encountered. Out of all the participants, 85% had prior experience with DUR alerts. However, 40% of them expressed dissatisfaction with the alerts. Moreover, 88% of the participants received highly frequent DUR alerts, but only 40% believed that DUR alerts could identify rare adverse drug reactions. Additionally, only 27% of the participants altered their prescriptions based on alerts for the MAOI/serotonin modulator. The survey showed that 66% of participants believe improvements are necessary for the DUR system. Specifically, 77% of participants felt that more information is needed on overlapping prescriptions, 82% on patients with chronic diseases, and 82% on potential reactions caused by co-administration. At the same time, 75% raised concern about the need for backup for any server breakdown. Positive perceptions about DUR lead to changing the prescription in response to an alert. Therefore, improving the DUR system is crucial to prevent pharmacists from missing important alerts and to increase their awareness of clinically significant alarm signals. By doing so, we can optimize patient safety and contribute to providing high-quality healthcare services.